Identification of sociotechnical changes caused by Industry 4.0 - Felix Schnasse; Jörn Steffen Menzefricke; Stefan Gabriel; Daniela Hobscheidt; Matthias Parlings; Arno Kühn; Roman Dumitrescu (Data Science and Innovation in Supply Chain Management: How Data Transforms the Value Chain. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 29, 2020)
Purpose: Industry 4.0 provides significant potentials for companies. Despite the promising opportunities, companies, especially SME, are still hesitant to implement new technologies. The main reasons are far-reaching changes with respect to the socio-technical dimensions causing risks that are difficult to assess. This research provides a methodology to identify these socio-technical changes for Industry 4.0 use cases. Methodology: Based on the three Design Science Research Cycles, a procedure and the corresponding methods for identifying socio-technical changes and risks during the introduction of Industry 4.0 will be designed. Findings: The developed tool enables the derivation of use-case specific changes and risks in the socio-technical dimensions of human, technology and organization. These interactions have to be considered when introducing Industry 4.0 use cases in order to ensure a promising usage. In addition, the need for further research in the field of socio-technical risk management is identified. Originality: Classical approaches do not address socio-technical interdependencies during the implementation of Industry 4.0 solutions. To bridge this gap, this methodological approach combines risk management and the concept of socio-technical system design.
urn:nbn:de:gbv:830-882.0115313; hdl:10419/228914; https://econpapers.repec.org/RePEc:zbw:hiclpr:29
Keywords: 650; Logistics; Industry 4.0; Digitalization; Innovation; Supply Chain Management; Artificial Intelligence; Data Science